Retinal microvasculature and imaging markers of brain frailty in normal aging adults - Tao, Wendan; Kwapong, William Robert; Xie, Jianyang; Wang, Zetao; Guo, Xiaonan; Liu, Junfeng; Ye, Chen; Wu, Bo; Zhao, Yitian; Liu, Ming (Frontiers in Aging Neuroscience, 2022)
Background: The retina and brain share similar embryologic origin, blood barriers, and microvasculature features. Thus, retinal imaging has been of interest in the aging population to help in the early detection of brain disorders. Imaging evaluation of brain frailty, including brain atrophy and markers of cerebral small vessel disease (CSVD), could reflect brain health in normal aging but costly and time consuming. In this study, we aimed to evaluate the retinal microvasculature and its association with radiological indicators of brain frailty in normal aging adults. Methods: Swept-source optical coherence tomography angiography (SS-OCTA) and 3T-MRI brain scanning were performed on normal aging adults (aged ≥50 years). Using a deep learning algorithm, microvascular tortuosity(VT) and fractal dimension parameter (Dbox) were used to evaluate the superficial vascular complex (SVC) and deep vascular complex (DVC) of the retina. MRI markers of brain frailty include brain volumetric measures and CSVD markers were assessed. Results: Of the 139 normal aging individuals included, the mean age was 59.43 ± 7.31 years, and 64.0 % (n=89) of the participants were females. After adjustment of age, sex, and vascular risk factors, Dbox in the DVC showed a significant association with the presence of lacunes (β=0.58, p=0.007) while VT in the SVC significantly correlated with the score of cerebral deep white matter hyperintensity (β=0.31, p=0.027). No correlations were found between brain volumes and retinal microvasculature changes (p > 0.05）. Conclusions: Our report suggests that imaging of the retinal microvasculature may give clues to brain frailty in the aging population.